Urine and plasma metabonomics coupled with UHPLC-QTOF/MS and multivariate data analysis on potential biomarkers in anemia and hematinic effects of herb pair Gui-Hong. (21st July 2015) - Li, Shujiao; Lin, Hang; Qu, Cheng; Tang, Yuping; Shen, Juan; Li, Weixia; Yue, Shijun; Kai, Jun; Shang, Guanxiong; Zhu, Zhenhua; Zhang, Changbin; Liu, Pei; et al.
Absrtract: Ethnopharmacological relevance: The compatibility of Angelicae Sinensis Radix (Danggui) and Carthami Flos (Honghua), a famous herb pair Gui-Hong, can produce synergistic and complementary hematinic effects. Our previous studies have indicated that Gui-Hong has therapeutic potential treatment in hemolytic and aplastic anemia (HAA). The present study aimed to investigate the hematinic effects of Danggui, Honghua and Gui-Hong on HAA rats induced by acetyl phenylhydrazine (APH) and cyclophosphamide (CP) and to explore the underlying hematinic regulation mechanisms. Materials and methods: Rats were divided into 5 groups, and drugs were administered by oral gavage one time each day for continuous 7 days from the experiment began. Urine and plasma were analyzed by ultra-high-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UHPLC-QTOF/MS). Partial least-squares discriminate analysis (PLS-DA) models were built to evaluate the therapeutic effects of Danggui, Honghua and Gui-Hong. Pearson correlation matrix analysis method was used to discover the correlations between potential biomarkers and biochemical indicators of HAA rats. Results: Seven potential biomarkers contribute to the separation of model group and control group were tentatively identified. The levels ofl -kynurenine, phenylalanine, nicotinic acid and sphingosine increased significantly ( P <0.05) in HAA rats, while the levels ofl -isoleucine, l -tyrosine and serotonin decreased significantly ( P <0.05) in comparison with control rats. Those endogenous metabolites were chiefly involved in phenylalanine, tyrosine and tryptophan biosynthesis, valine, leucine and isoleucine biosynthesis, tryptophan metabolism and tyrosine metabolism. The metabolic deviations could be regulated closer to normal level after Danggui, Honghua and Gui-Hong intervention. In term of hematinic effects, Gui-Hong was the most effective as shown by the relative distance in PLS-DA score plots and relative intensity of potential biomarkers. The result reflected the synergic action between Danggui and Honghua. The above results were found to be reasonable in explaining the hematinic effects mechanism of Gui-Hong. Conclusions: The results of routine blood, urinary metabolic pattern and plasma metabolic pattern show the Danggui, Honghua and Gui-Hong groups are moving toward the control group and the HAA was being prevented and alleviated. The effect of Gui-Hong group is more remarkable than Danggui and Honghua groups. Some potential biomarkers likel -kynurenine, phenylalanine, l -isoleucine, l -tyrosine, serotonin, nicotinic acid and sphingosine have been found and identified. The work shows that the metabonomics method is a promising tool in the efficacy and mechanism research of traditional Chinese medicines. Graphical abstract: